Pulmonary function test in Tropical Pulmonary Eosinophilia - Ratan Kumar; Sudhir Mourya (International Journal of Medical Research and Review, 2014)
Introduction: Tropical pulmonary eosinophilia (TPE) is a syndrome of wheezing, fever and eosiniphilia seen predominantly in the Indian subcontinent and other tropical areas. The syndrome results from immunologic hyper-responsiveness to human filarial parasites, Wuchereria bancrofti and Brugia malayi. Absolute eosinophilia counts are usually more than 3,000 cells/mm3. Lung functions are severely compromised. Pulmonary function tests may show a mixed restrictive and obstructive abnormality with a reduction in diffusion capacity. The mean values of expiratory flow rates were significantly decreased. Oral DEC (6 mg/kg per day) for 3 weeks is treatment of choice.Methods: A total of 61, clinic-radiologically and haematologically suspected cases of tropical pulmonary eosinophilia were included in study along with 39 healthy controls. Pulmonary functions, which included forced vital capacity (FVC), forced expiratory volume in one second (FEV1), FEV1/FVC Ratio, maximum mid expiratory flow rate (MMEFR) and peak expiratory flow rate (PEFR) were observed in study cases and control.Results: The mean values ±S.D. of all spirometric parameters showed low value in cases in comparison to control. Statistically all parameters showed highly significant difference (‘p’ value were <0.001) except in FEV1/FVC ratio (‘p’ value was >0.05). After the treatment with DEC the mean values ± S.D. of all parameters in cases showed improvement but the values were remained still below the control value.Conclusion: This disease, if left untreated or treated late, may lead to long-term sequelae of pulmonary fibrosis or chronic bronchitis with chronic respiratory failure.